Asuhan Keperawatan Pada An. K Dengan Bronkopneumonia Di Ruang Sahabat RSUD Bangkinang Tahun 2025 - Mahmudah, Indria; Hidayat, Ridha; Safitri, Yenny; Nurman, Muhammad (El-Emir Institute, 2025)
Bronchopneumonia is one of the acute respiratory infections that affects the lungs, especially in children, with a high incidence rate in Indonesia, including at RSUD Bangkinang. Based on 2024 data, bronchopneumonia ranked second among the top ten inpatient diseases at RSUD Bangkinang. This study aims to provide an overview of the nursing care implementation for children with bronchopneumonia at RSUD Bangkinang in 2025. This research employed a case study approach on an 11-month-old child admitted with a medical diagnosis of bronchopneumonia. The nursing care was conducted over three days, covering assessment, nursing diagnoses, planning, implementation, and evaluation. The identified nursing diagnoses were: ineffective airway clearance, hyperthermia, and nutritional deficit. After three days of nursing interventions, the patient’s condition improved, as indicated by reduced shortness of breath, decreased body temperature, and increased appetite. The interventions included airway management, hyperthermia management, and nutritional management based on the Indonesian Nursing Intervention Standards (SIKI). Proper and comprehensive nursing care for children with bronchopneumonia can accelerate recovery and prevent further complications. Observational, therapeutic, educational, and collaborative interventions are essential in handling pediatric bronchopneumonia cases.